Education and Health in Sub-Saharan Africa : A Review of Sector-Wide Approaches - World Bank (Washington, DC, 2013)
Dissatisfaction with traditional project approaches and a recognition of the limitations of the sector adjustment programs led to the development of new lending instruments to improve the impact of development assistance on the sector as a whole. Within the Africa region of the World Bank, the most commonly used such instrument to rpovide support for a more comprehensive sector development program has become known as the "sector investment program (SIP)." In recent years this approach--characterized by a government-led partnership with key external partners, based on a comprehensive sector policy and expenditure framework, and relying on government institutions and common procedures for implementation--has been used by the World Bank for about a dozen operations in the health and education sectors in Sub-Saharan Africa. This report reviews the experience to date of the Africa region in the Bank with this approach: it summarizes the lessons learned, identifies the strengths and weaknesses of this approach, and provides guidance and advice to operation staff in the Bank as well as partner agencies and governments who will be involved in sector-wide approaches in the year to come.